At home : an anthropology of domestic space - Cieraad, Irene; Short, John R. (Space, place, and society, 1999)
In a volume that brings together a wide range of disciplines - art history, sociology, architecture, cultural anthropology, and environmental psychology - Irene Cieraad presents a collection of articles that focuses on the practices and symbolism of domestic space in Western society. These essays go beyond the discussion of conventional issues such as aesthetics and social standing. At Home takes an in-depth anthropological look at how different cultures use their homes as a visual model of the culture's social structure.